Multiple wavelengths generation utilizing nonlinear optics of four wave mixing - Cholan, Noran Azizan (2014)
The response turns from linear to nonlinear when high intensity waves propagate in optical fibers, causing the emergence of nonlinear phenomena such as stimulated Brillouin scattering (SBS) and four wave mixing (FWM). While that phenomena cause optical communication systems to deteriorate, they are nevertheless useful for certain applications such as in multiple wavelengths generation. This dissertation presents experimental work that involves the manipulation of FWM in the developments of lasers and cascades. Four main research studies are successfully demonstrated in efforts to improve the performance of FWM-based lasers and cascades. The first study is related to multiwavelength BEFLs. Despite the advantage of wide tunability, they unfortunately suffer from the laser output flatness due to the nature of cascaded SBS processes. In this work, FWM in an optical fiber is applied to the laser lines of a multiwavelength BEFL through the incorporation of residual waves in order to make the output flat. Comparisons between the BEFL with and without the assistance of FWM suggest the effectiveness of the proposed technique. With the assistance of FWM, the uniformity or flatness records a 3.73 dB improvement as compared to the case without the assistance of FWM when the Brillouin pump is set to 1550 nm. The second research work is related to an experimental study on the residual waves of multiwavelength BEFLs. Experimental results suggest that the properties of residual waves are influenced by FWM. Multiple FWM processes in fibers are believed to cause the output power of the residual waves to grow gradually and the value of optical-signal-to-noise ratio to be lower due to the power sharing basis of FWM processes. The third research work, on the other hand, is aimed to improve continuous tunability of erbium-doped fiber lasers (EDFLs) in which the stability is obtained from multiple FWM processes in optical fibers. With the incorporation of tunable bandpass filters in the laser cavity, a proposed dual wavelength EDFL can achieve continuous wavelength spacing from 0.52 nm to 22.78 nm, limited only by the gain bandwidth of the erbium-doped fiber amplifier and the linewidth of filters. In the fourth research work, FWM cascades without external laser sources and modulators is proposed in a bid to reduce the complexity of the system. The need for laser sources is catered by a dual wavelength EDFL which acts as an intracavity pump, while the requirement for pump modulators for SBS suppression is tackled by the broad linewidth of the EDFL. In summary, four research studies that are related to FWM in generating multiple wavelengths are experimentally demonstrated in this thesis. The first two studies focus on improvements in BEFLs, while the third and fourth study is for enhancements in EDFLs and FWM cascades respectively. All the four studies are found to be effective in elevating the performances and understanding of FWMbased lasers and cascades to further heights.